1994
DOI: 10.1073/pnas.91.9.3789
|View full text |Cite
|
Sign up to set email alerts
|

Na(+)-I- symport activity is present in membrane vesicles from thyrotropin-deprived non-I(-)-transporting cultured thyroid cells.

Abstract: The active accumulation of I-in the thyroid gland is mediated by the Na+-I-symporter and driven by the Na+ gradient generated by the Na+/K+-ATPase. Thyrotropin (TSH) stimulates thyroidal I accumulation. Rat thyroidderived FRTL-5 cells require TSH to accumulate I-. TSH withdrawal for over 7 days results in complete loss of Na+-Isymport activity in these cells [Weiss, S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
2
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 34 publications
(27 reference statements)
3
65
2
3
Order By: Relevance
“…The e ects of Ras transformation on Pax-8 expression have not yet been reported, although reduced levels of Pax-8 expression have been observed in follicular adenomas (Heldin and Westermark, 1991) and in thyroid cells expressing mutated p53 (Battista et al, 1995). RasC40-dependent signals might also downregulate the expression and/or activity of a recently described novel thyroid transcription factor involved in the regulation of NIS expression (Ohmori et al, 1998), or could a ect NIS activity through a post-transcriptional mechanism similar to that observed for TSH (Kaminsky et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The e ects of Ras transformation on Pax-8 expression have not yet been reported, although reduced levels of Pax-8 expression have been observed in follicular adenomas (Heldin and Westermark, 1991) and in thyroid cells expressing mutated p53 (Battista et al, 1995). RasC40-dependent signals might also downregulate the expression and/or activity of a recently described novel thyroid transcription factor involved in the regulation of NIS expression (Ohmori et al, 1998), or could a ect NIS activity through a post-transcriptional mechanism similar to that observed for TSH (Kaminsky et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In tissues expressing mature hNIS and showing the classical basolateral plasma membrane staining, intracellular hNIS immunoreactivity was also found; it would correspond to hNIS in the course of synthesis and trafficking toward and from the plasma membrane. 21,22 It is noteworthy that the observations made on hypofunctioning tumors applied in all respects to nonstimulated NT. Indeed, nonstimulated NT samples from patients under T 4 treatment contained hNIS transcripts and only low amounts of nonglycosylated hNIS.…”
Section: Discussionmentioning
confidence: 99%
“…However, significant iodide uptake is observed only in follicle-forming thyrocytes, indicating the importance of cell polarization and spatial organization for functional activity of NIS [45]. Kaminsky et al (1994) reported persistent NIS activity in membrane vesicles prepared from FRTL-5 cells following prolonged TSH withdrawal. Interestingly, no such activity was detected in intact cells in similar conditions [46].…”
Section: Post-transcriptional Regulation Of Nismentioning
confidence: 99%
“…Kaminsky et al (1994) reported persistent NIS activity in membrane vesicles prepared from FRTL-5 cells following prolonged TSH withdrawal. Interestingly, no such activity was detected in intact cells in similar conditions [46]. This could be explained by the differential cellular expression of NIS following TSH deprivation.…”
Section: Post-transcriptional Regulation Of Nismentioning
confidence: 99%